The economic impact of oil spill on communities in Imo State and the Niger Delta Region of Nigeria - Isidiho, Alphonsus O. (Tanjong Malim, 2020)
The economic impact of oil spill on communities in Imo State and the Niger Delta Region of Nigeria by Isidiho, Alphonsus O.